Interpreting Pesticide Label Wording - Frederick M. Fishel (EDIS)
Pest problems occur in diverse settings from agricultural to commercial and residential. In Florida, pest control is a year-round consideration and many times a pesticide will be chosen as part of the management plan for the problem. If a pesticide will be part of the management plan, understanding the contents of the pesticide label is essential for the product's safe and effective use. This document is PI-34, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.